Persinggungan Kepemimpinan Transformational Dengan Kepemimpinan Visioner Dan Situasional - Toha Ma'sum (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2019)
The success or failure of an organization to achieve its intended goals is very dependent on the ability of its leaders to establish a climate of cooperation easily and can mobilize existing resources so that they can use them and can run effectively and efficiently. Thus the life of an organization is largely determined by the role of a leader. This study focuses on knowing and describing the basic concepts of leadership, transformational leadership, visionary leadership, situational leadership concepts, and then analyzing the intersection of transformational leadership with visonary and situational leadership. This study uses a type of library research with a qualitative approach, namely research that does not carry out numerical data calculations (quantitative). In this library research, the method of data collection is a method of documentation, which is in the form of books, notes, transcripts, newspapers, magazines, journals, and so on. For the data analysis process, the technique chosen is a descriptive analysis analysis technique using a series of logical thinking systems that can be used to construct a number of concepts into propositions, hypotheses, postulates, axioms, assumptions, or constructs into theories. The results of this study are that transformational leadership, visionary, and situational basically have similarity, namely prioritizing the completion of work and mutual success of subordinates, leadership is accepted by all subordinates and there is a clear division of labor between individuals. The teamwork and success of the team is the main target. Transformational, Visionary, and situational leadership in carrying out their leadership are very innovative, creative and active in carrying out and solving problems faced. On the other hand, Transformational, Visionary, and situational leadership is strongly influenced by the personal abilities of leaders and subordinates of the leader, in the sense that success is strongly influenced by the existence of togetherness in a team. Basically, transformational leadership, with visionary and situational leadership is a leadership model that has three weaknesses and strengths. In carrying out leadership, one can run all three, and / or one of them to achieve goals. However, everything is greatly influenced by the individual abilities of the leader.